Catalytic activities of Ni-decorated boron particles. (5th July 2017) - Jung, Hye Jin; Nam, Kyusuk; Lee, Jisuk; Han, Doo-Hee; Sung, Hong-Gye; Hyun, Hyung Soo; Sohn, Youngku; Shin, Weon Gyu
Abstract: Ni-decorated boron (Ni/B) particles were prepared by a ball-milling method, and their physicochemical properties were fully characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD) analysis, high-resolution transmission electron microscopy (HRTEM), energy-dispersive X-ray spectroscopy (EDX) elemental mapping, and X-ray photoelectron spectroscopy (XPS). Upon decoration by Ni, the previously inactive boron particles showed enhanced activity in CO oxidation and photoelectrochemical hydrogen/oxygen evolution reactions (HERs/OERs). The CO oxidation onset and T 10% were observed around 320 and 350 °C, respectively. In preliminary tests, the Ni/B (1:3 w/w) sample showed UV and visible light current responses, and current densities of 600 and 240 μA/cm 2 were observed at a potential of 500 mV for HER and OER, respectively. The present study emphasizes the potential application of boron as a catalyst support material for air quality control and photoelectrochemical hydrogen/oxygen evolution. Graphical abstract: Highlights: Ni-decorated boron (Ni/B) particles were prepared by a ball-milling method. B particles showed enhanced activity in CO oxidation upon Ni-decoration. Ni/B particles showed photoelectrochemical hydrogen/oxygen evolution reactions.